2009
DOI: 10.1080/03014223.2009.9651471
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pest–management operations on the abundance and size–frequency distribution of the New Zealand endemic frogLeiopelma hochstetteri

Abstract: in New Zealand, introduced mammals, especially rats, have been considered a primary factor in the extinction of amphibians. Leiopelma hochstetteri is a riparian frog, and is the most widespread of the surviving species of native frogs in New Zealand. at present, all populations of this frog species coexist with introduced mammals, which in some cases have been subject to pest-management operations without monitoring the potential benefits or damage to the frogs. We investigated the influence of a 7-year rat ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…According to the New Zealand River Environment Classification (MfE 2004), the channels of erosive streams with volcanic acidic geology tend to be steep and covered by coarse substrates (i.e. boulders and cobbles); steep-sloped stream channels covered by coarse substrates have been found to be positively associated with frog abundance (Nájera-Hillman et al 2009a), and this study indicates that they are also positively associated with frog distribution. Furthermore, it has been noted that L. hochstetteri is vulnerable to any disturbance that affects substratum stability (Tessier et al 1991), particularly, severe storms that cause sudden flooding (McLennan 1985); streams with small catchment areas are less susceptible to flooding than those with large catchment areas (Gregory et al 1991).…”
Section: Relationship Between Frog Distribution and Environmental Chamentioning
confidence: 75%
See 2 more Smart Citations
“…According to the New Zealand River Environment Classification (MfE 2004), the channels of erosive streams with volcanic acidic geology tend to be steep and covered by coarse substrates (i.e. boulders and cobbles); steep-sloped stream channels covered by coarse substrates have been found to be positively associated with frog abundance (Nájera-Hillman et al 2009a), and this study indicates that they are also positively associated with frog distribution. Furthermore, it has been noted that L. hochstetteri is vulnerable to any disturbance that affects substratum stability (Tessier et al 1991), particularly, severe storms that cause sudden flooding (McLennan 1985); streams with small catchment areas are less susceptible to flooding than those with large catchment areas (Gregory et al 1991).…”
Section: Relationship Between Frog Distribution and Environmental Chamentioning
confidence: 75%
“…ship rats) and disease (Towns & Daugherty 1994, Baber et al 2006, Bishop et al 2009). However, Nájera-Hillman et al (2009a) did not find conclusive evidence that ship rats are a threat, and, despite extensive surveys, the amphibian disease caused by the fungus Batrachochytrium dendrobatidis has not been detected in L. hochstetteri (Bishop et al 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, a non-native predator may interact with both non-native and native prey within an ecosystem [8]. In such a situation, predicting which type of prey will dominate following the removal of the non-native predator is crucial [8][9][10][11], because the response of the prey community to the predator removal is contextdependent [12][13][14]. Theoretical studies have indicated that eradicating non-native apex predators results in the outbreak of non-native prey and induces severe declines in native prey populations if the non-native prey are either superior competitors or are mesopredators of the native prey (termed the mesopredator release effect) [9].…”
Section: Introductionmentioning
confidence: 99%
“…al. 1991;Whitaker & Alspach 1999;Na´jera-Hillman et al 2009). Only a few surveys have included seeps and river banks (McLennan 1985), and no survey work has specifically targeted seeps and stream emergence sites.…”
Section: The Duration Of Frog Metamorphasismentioning
confidence: 99%